2020
DOI: 10.21037/jhmhp.2019.12.02
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and self-care activities among Sudanese individuals with diabetes: a cross sectional survey

Abstract: Background: Increasing knowledge and self-care practices may lead to adequate glycemic control and decrease diabetes complications. Therefore, the aim of the current study was to determine the knowledge and self-care activities among Sudanese individuals with diabetes.Method: A cross-sectional study was conducted in four centers of diabetes in Khartoum state (286 participants). The respondents were interviewed using a set of validated questionnaires. The data collected were analyzed using the statistical packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…On the same line, ALHargan et al (2019) reported that, self-care practices of DR patients were found to be low. On the contrary, a Sudanese study by Farag et al (2020) revealed that, most patients had an acceptable level of practice. The possible explanation for inadequate self-care practices level for both groups at the preintervention phase could be due to low educational level of patients that leaded to having a deficient level of knowledge about DR and consequently about proper self-care practices.…”
Section: Self-care Practices Of the Studied Groups During Different P...mentioning
confidence: 92%
“…On the same line, ALHargan et al (2019) reported that, self-care practices of DR patients were found to be low. On the contrary, a Sudanese study by Farag et al (2020) revealed that, most patients had an acceptable level of practice. The possible explanation for inadequate self-care practices level for both groups at the preintervention phase could be due to low educational level of patients that leaded to having a deficient level of knowledge about DR and consequently about proper self-care practices.…”
Section: Self-care Practices Of the Studied Groups During Different P...mentioning
confidence: 92%
“…about "Knowledge, Attitude, and Practices (KAP) of Diabetics towards diabetes and diabetic retinopathy in Riyadh, Saudi Arabia" their stthat the overall practices score of DR patients was below the accepted range. On the contrary, a Sudanese study by Farag et al (2020) revealed at their study about "Knowledge and self-care activities among Sudanese individuals with diabetes" that most patients had an acceptable level of selfcare practice. The possible explanation for inadequate self-care practices level for both groups at the pre-intervention phase could be due to low educational level of patients that lead to having deficiency of knowledge about DR and consequently about proper selfcare practices.…”
Section: Effectiveness Of Educational Intervention On Self-care Pract...mentioning
confidence: 95%